PERMASALAHAN PENGAKUAN TERHADAP KELOMPOK-KELOMPOK BELLIGERENT DARI SEGI HUKUM HUMANITER INTERNASIONAL - Marcel Gabriel Pailalah; Sulaiman Hamid; Chairul Bariah (Journal of USU International Law, 2017)
ABSTRACTWars and conflicts have always been a human habit throughout civilization, from the very beginning of human creation on Earth, warfare has always been a determinant of human survival and especially the standing or destruction of civilizations existing in the world. Of the many conflicts that exist, the conflict is a revolt that attracts attention, because of the conflict between the ruling government against armed parties who are not satisfied with the relevant government policy. From here comes the term "belligerent", which means the parties to the dispute or the rebels. At first, belligerent created from the dissatisfaction of the elements of the people against the government in a country. The ruling government is unable to accommodate the will and interests of these dissatisfied elements of the people, so that they rebel in order to realize their neglected aspirations. This initially limited rebellion gradually began to spread to every territory of the country, and the rebels were able to control various territories and establish their own version of government. This situation also received attention from the world, and for some considerations of the international community, the rebels were recognized as a separate entity representing the aspirations of elements of the people who are not satisfied with the regime in power in a country. The research method used is normative juridical by doing research of literature study to obtain secondary data needed in the framework of completion of this thesis. The results are presented descriptively and with related drawings of the materials discussed in order to obtain an explanation of the existing problems. The research in this thesis aims to find out the meaning of armed conflict in international humanitarian law, belligerent and its history, recognition conditions and worldviews of belligerent groups, and internationally recognized belligerent groups.   Key Words: War and conflict, rebellion, armed conflict in International Humanitarian Law, belligerent.